Biblia i filozofia w konfrontacji Bazylego Wielkiego z apolinaryzmem - Paczkowski, Mieczysław C. (Vox Patrum, 2018)
This article presents the role played by philosophy and biblical exegesis in controversy with Apollinarius of Laodicea. First of all it tries to present the general context of the dispute, then to develop Basil’s theological thinking and apply it to the problematic Christological field, where Apollinarius directed his challenge. Faced with the anthropological-soteriological problem relating to the defence of the integrity of Christ’s human nature, Basil draws on Stoic and Neoplatonic philosophical tradition. Then, this paper focuses attention on Basil’s interpretation of some biblical passages in the confutation of Apollinaris’ doctrine. Basil had started the controversy by describing Apollinarius as supporter of fabulous theories, which are not based on the Scriptures, and of Judaizing ideas which concerned the eschatological renewal. Generally, the Cappadocian prefers to distance himself from Apollinaris and does not intervene in complete manner on the theological debate. The bishop – monk tries to unmask the errors of the opponents’ theories starting with the correct interpretation of the scriptural passages used by Apollinarius. In some points of his works, the Cappadocian insists that the Savior had a soul capable of feeling and suffering. According to the bishop of Caesarea some of anthropological and philosophical principles used by Apollinaris, along with the distorted reading of biblical texts, revealed the ambiguities and the inconsistencies of his arguments.